2011
DOI: 10.1111/j.1526-4637.2011.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Abdominal Wall Pain and Ultrasound-Guided Abdominal Cutaneous Nerve Infiltration: A Case Series

Abstract: Ultrasound can reliably be used for infiltration of the abdominal cutaneous nerves. This will improve the safety as well as diagnostic utility of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 6 publications
(4 reference statements)
1
41
0
Order By: Relevance
“…These results were confirmed in a volunteer study where a nerve stimulator was used [3]. In a series of 20 patients with meralgia paresthetica, all had resolution of their symptoms within 2 weeks of injection; however, four patients required repeat injections at 1 week [73] • • Other US-guidance has also been described for injections of the ganglion of impar [75], pudendal nerves [76] and abdominal cutaneous nerves [77]. These studies demonstrated feasibility of the methods rather than superiority of the technique.…”
Section: • Lateral Femoral Cutaneous Nervesupporting
confidence: 57%
“…These results were confirmed in a volunteer study where a nerve stimulator was used [3]. In a series of 20 patients with meralgia paresthetica, all had resolution of their symptoms within 2 weeks of injection; however, four patients required repeat injections at 1 week [73] • • Other US-guidance has also been described for injections of the ganglion of impar [75], pudendal nerves [76] and abdominal cutaneous nerves [77]. These studies demonstrated feasibility of the methods rather than superiority of the technique.…”
Section: • Lateral Femoral Cutaneous Nervesupporting
confidence: 57%
“…The main advantages of the ultrasound-guided blocks are the accuracy of injections and the reduction of risk since the injection is performed in real time. Kanakarajan et al5 published a case series of nine patients suffering from ACNES who were diagnosed by clinical symptoms combined with a positive Carnett’s sign. All patients were treated with an ultrasound-guided infiltration of the abdominal cutaneous nerves at the site of maximum tenderness and the lateral border of the rectus abdominis muscle.…”
Section: Ultrasound-guided Blocksmentioning
confidence: 99%
“…Anatomically, the lower intercostal nerves (T8–T12) run between the internal oblique and transversus abdominis muscles, up to the point where they reach the rectus abdominis; here, they make a turn in their course to enter the rectus channels (commonly five at each abdominal side) 5,6. Some authors have suggested that the entrapment is usually caused by this sudden turn in their course into the rectus abdominis channel, leading to ACNES 1,7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C hronic abdominal and flank pain can be multifactorial 1 and difficult to treat. Loin pain hematuria syndrome (LPHS) is a rare clinical cause of chronic abdominal and flank pain and is a diagnosis of exclusion.…”
mentioning
confidence: 99%